Time trends and heterogeneity in the disease burden of visual impairment due to cataract, 1990–2019: A global analysis - Han, Xiaotong; Zou, Minjie; Liu, Zhenzhen; Sun, Yi; Young, Charlotte Aimee; Zheng, Danying; Jin, Guangming (Frontiers in Public Health, 2023)
Objectives This study aimed to estimate the disease burden of cataract and evaluate the contributions of risk factors to cataract-associated disability-adjusted life years (DALYs). Materials and methods Prevalence and DALYs of visual impairment due to cataract were extracted from the Global Burden of Disease (GBD) study 2019 to explore time trends and annual changes. Regional and country-level socioeconomic indexes were obtained from open databases. The time trend of prevalence and DALYs was demonstrated. Stepwise multiple linear regression was used to evaluate associations between the age-standardized rate of DALYs of cataract and potential predictors. Results Global Prevalence rate of visual impairment due to cataract rose by 58.45% to 1,253.9 per 100,000 population (95% CI: 1,103.3 to 1,417.7 per 100,000 population) in 2019 and the DALYs rate rose by 32.18% from 65.3 per 100,000 population (95% CI: 46.4 to 88.2 per 100,000 population) in 1990 to 86.3 per 100,000 population (95% CI: 61.5 to 116.4 per 100,000 population) in 2019. Stepwise multiple linear regression model showed that higher refractive error prevalence (β = 0.036, 95% CI: 0.022, 0.050, P < 0.001), lower number of physicians per 10,000 population (β = −0.959, 95% CI: −1.685, −0.233, P = 0.010), and lower level of HDI (β = −134.93, 95% CI: −209.84, −60.02, P = 0.001) were associated with a higher disease burden of cataract. Conclusion Substantial increases in the prevalence of visual impairment and DALYs of cataract were observed from 1990 to 2019. Successful global initiatives targeting improving cataract surgical rate and quality, especially in regions with lower socioeconomic status, is a prerequisite to combating this growing burden of cataract in the aging society.